LAGOPHTHALMOS DRIVERS IN LOCOMOTIVES - Adnan Alam Khan; Huma Jamshed; Tahira Ansari; Ahmad Bilal; Urooj Waheed (Spectrum of Engineering Sciences, 2025)
Every individual desires a restful night’s sleep on a comfortable bed, free from stressors. Many people invest thousands of dollars in their quest for a good night's sleep. Medical studies indicate that nearly 20% of individuals sleep with their eyes open, leading others to mistakenly perceive them as awake. This condition, known as Lagophthalmos, arises from issues with facial nerves or muscles. Symptoms include weight loss, clumsiness, eye-open sleep, and fatigue. In Western countries, those affected often adopt dogs, whose primary role is to monitor their owners. If the patient’s eyes remain open, the dog will bark loudly until they awaken. This study proposes a solution in which a camera monitors the patient via their laptop; when the patient enters an unconscious state, the system will initiate a call to their mobile phone to rouse them from sleep.